Development of a Satellite Nozzle-Thruster Design for Geostationary Orbit Deployment: CFD-Based Geometric Optimization for RIDU-Sat - Ahmad Dzakir Nurafif Mahdin; Sumaryadi; Ansori (PT FORMOSA CENDEKIA GLOBAL, 2026)
The development of an efficient nozzle-thruster is crucial for the RIDU-Sat nanosatellite to reach and maintain geostationary orbit (GEO) with minimal propellant consumption. This study optimizes the geometry of a convergent-divergent nozzle through Computational Fluid Dynamics (CFD) using ANSYS Fluent with hydrogen peroxide as the monopropellant. Three throat diameter variations (0.5 mm, 1 mm, and 2 mm) were tested with a convergent angle of 45° , and a divergent angle of 30° . The results show that the design with a 0.5 mm throat diameter produces the highest exit velocity (1740 m/s), thrust (609 mN), and specific impulse (177 s). The smaller the throat diameter, the higher these three performance parameters become due to more effective supersonic expansion. These findings provide an optimal nozzle design that can improve propulsion efficiency for the geostationary orbit deployment and maintenance maneuvers of RIDU-Sat.